Structural-Semantic Characteristics of Modern German Phraseologisms with the Phraseologically Linked Formative - Pavlyshynets, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
This article is an attempt to define the classification criteria of phraseological units, which have a phraseologically linked formative in their structure. In this article we come up with the respective classification criteria according to the features of the structure and the semantics of the determined phraseologisms. Within this research phraseological units with the phraseologically linked formative are classified according to grammatical, structural-semantic and semantic criteria, in accordance with the national specificity, which is characteristic of these phraseologisms. By combining different classification criteria we attempted to determine the nucleus and the periphery of the phraseological units with the phraseologically linked formative